Brunei and Malaysia Relationship in Pelita Brunei, 1957-1970 / Mohd Azhar Zainal - Zainal, Mohd Azhar; Abdullah, Mohd Firdaus; Sulaiman, Yusry (Faculty of Communication and Media Studies (FCMS), 2023)
Over the years most studies conducted on the relationship between Brunei and Malaysia did not consider Pelita Brunei newspaper as the main source of research despite the newspaper is considered the official discourse by the Government of Brunei since 1956. In fact, the newspaper plays an important role in providing information related to the relationship between Brunei and Malaysia in the period specified. Therefore, this study attempts to uncover the extent to which Brunei and Malaysia’s relationship issues affect Pelita Brunei’s reporting from the period of 1957 to 1970. This research has a historical theme and fully uses qualitative methods. Sources and materials are obtained from major archives and libraries such as the National Archives of Malaysia, the National Archives of Brunei Darussalam, the National Library of Malaysia, and local university libraries throughout Malaysia and other countries. The results of the study found that Pelita Brunei played an important role in conveying issues related to the relationship between Brunei and Malaysia from 1957 until 1970. The newspaper also became one of the main mediums in the Brunei Government’s efforts to form their own nation state. At the same time, it can be seen that several important issues related to the relationship between Brunei and Malaysia became the focus of this newspaper during the period mentioned. For example, issues related to the formation of Malaysia, education and security issues of Brunei were highlighted during the period.